Guide :

if f(x)=2x^3-5x+6, what is x if f(x+1)-f(x)=0

Please some help on this question

Research, Knowledge and Information :

f(x) 2 h NOTE - California State University, Northridge

For P(x) = 2x 3 + 5x 2 – 15x + 6, a. ... ½ 2 5 –15 6 The zero remainder tells us x – ½ is a FACTOR of P(x). 1 3 –6 2 6 –12 0 Thus ½ is a ROOT ...
Read More At : www.csun.edu...

'f(x)'='(x + 5x+6)/(x+ 2x-3) - Virginia Tech

p.'92'#'1,'3,'11,'15,'16 #'6,'7,'9 ... V.A.'(s)'of'f(x)'='(x 2+ 5x+6)/(x+ 2x-3) #'31,'40 4 2.3 Calculating'Limits'Using'the'Limit'Laws' ... F Fall'Break 0 7 4
Read More At : www.math.vt.edu...

The function is [math]f(x) =x^3-2x^2-5x+6.[/math] How do you ...

The function is [math]f(x) =x^3-2x^2-5x+6.[/math] How do you find the tangent on the graph of ... at the point of tangency, (1, 0), we have: Slope m = f ′(1) = 3(1 ...
Read More At : www.quora.com...

Math 234 March 27 - Mathematics - Illinois

Math 234 March 27 I. Di erentiate the ... f0(x) = [(2xe( x 3+5 +2x)+x2e( x3+5x+2x)(3x2+5+2 ln(2)))(3 x3 2+e 3x) ... (f(x)))0 = (2ln(x+ 3) + (1=4)ln(x2 + 3x+ 6) + 7ln ...
Read More At : www.math.uiuc.edu...

The function of [math]f[/math] is [math]f(x) =x^3-2x^2-5x+6 ...

To find the equation of the tangent line to the graph of the function f at the point (1, 0)), ... d/dx x^3 - 2x^2 - 5x + 6 (3)x^(3–1) - 2(2)x^(2–1) - 5(1)x^(1–1 ...
Read More At : www.quora.com...

MATH 10550, EXAM 1 SOLUTIONS Solution. - University of Notre Dame

MATH 10550, EXAM 1 SOLUTIONS 1. If f(2) = 5, f(3) = 2, f(4) = 5, g(2) = 6, g(3) = 2 and g(4) = 0, ... zero at x= 0 and x= 2. 6. If f(x) = (x2 + 3x)(6x5 2x8), compute ...
Read More At : www3.nd.edu...

f(x)=x^3-5x+1 - solution - GetEasySolution.com

Simple and best practice solution for f(x)=x^3-5x+1 equation. Check how easy it is, and learn it for the future. ... 3x-4=3x-7 | | 0.5x-4=2x+7 | | 5m=a | | 5(2+3x) ...
Read More At : www.geteasysolution.com...

Inverse Function f(x) = (x -1) / (2x + 3) - YouTube

Oct 26, 2011 · Inverse Function f(x) = (x -1) / (2x + 3) martin93003. Loading ... Composing f(x)=2x+1 and g(x)=(x-1)/2 - Duration: 2:59. calculuscoaches 6,193 views. 2:59.

Suggested Questions And Answer :

Simplify 16/4+{5x6-[3+(4+1)]}

16/4+{5*6-[3+(4+1)]} =16/4+{30-[3+5]} =16/4+{30-[8]} =16/4+{30-8} =16/4+{22} =4+22 =26

3,4,5,6 = 42 how?

3x4=12 5x6=30 12+30=42

5(x+6)+4(3x-7)

5(X + 6) + 4(3X - 7)          (I'll use 'X' for the letter x, and 'x' for multiplication) So first you need to multiply out the brackets, this means that 5(X + 6) + 4(3X - 7) = 5X + 5x6 + 4x(3X) + 4x(-7) = 5X + 30 + 12X - 28 = 17X + 2 So the final simplified equation is 5(x + 6) + 4(3x - 7) = 17X + 2

1+2(3+4)/(5x6)

me assume that stuf shood be 1+2*(3+4) / (5*6) =1+(2*7/30) =1+14/30 =1+0.46666666666... =2.46666666666...